Porungo cheese whey: β-galactosidase production, characterization and lactose hydrolysis - Marim,Aline Vitória Corim (2021)
Abstract This study evaluated the lactose hydrolysis by immobilized β-galactosidase, which was produced by Kluyveromyces marxianus using porungo cheese whey as substrate. Initially, the yeast was cultivated in porungo cheese medium at 30 °C and 200 rpm, showing a maximal β-galactosidase production of 14.19 U mL-1. The crude extract obtained was used to evaluate the enzymatic hydrolysis in lactose solution. The optimal pH and temperature of the free and immobilized enzyme was investigated, whereas the lactose hydrolysis was carried out using two enzyme solutions (total activities of 2 U and 6 U) for both forms of the biocatalyst. Ca-alginate immobilization of β-galactosidase increased optimal temperature range to 40 °C, compared to the value for the free enzyme, which was 37 °C. The optimal pH was also increased by immobilization to 7.0, from pH 6.5 observed for the free enzyme. The highest lactose hydrolysis conversion was 15.82% using 6 U of free enzyme and 13.77% for 2 U of immobilized enzyme. Although, free enzyme showed higher conversion rates in the initial reaction time, the immobilized enzyme kept operational stability throughout reaction time, suggesting the advantage of using this technology. The use of porungo cheese whey allowed to aggregate value to this agro-industrial by-product, with the concomitant production of β-galactosidase to be used in the food industry chain itself.